Detrital zircon ages and the origins of the Nashoba terrane and Merrimack belt in southeastern New England, USA - Hepburn, J. Christopher; Kuiper, Yvette D.; McClary, Kristin J.; Loan, MaryEllen L.; Tubrett, Michael; Buchwaldt, Robert (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2021)
The fault-bounded Nashoba–Putnam terrane, a metamorphosed early Paleozoic, Ganderian arc/back-arc complex in SE New England, lies between rocks of Avalonian affinity to the southeast and middle Paleozoic sedimentary rocks, interpreted as cover on Ganderian basement, in the Merrimack belt to the northwest. U–Pb detrital zircon laser ablation inductively coupled plasma mass spectrometry analysis were conduced on six samples from the Nashoba terrane in Massachusetts and seven samples associated with the Merrimack belt in Massachusetts and SE New Hampshire to investigate their depositional ages and provenance. Samples from the Nashoba terrane yielded major age populations between ~560 and ~540 Ma, consistent with input from local sources formed during the Ediacaran–Cambrian Penobscot orogenic cycle and its basement rocks. Youngest detrital zircons in the terrane, however, are as young as the Early to Middle Ordovician. Six formations from the Merrimack belt were deposited between ~435 and 420 Ma based on youngest zircon age populations and crosscutting plutons, and yielded large ~470–443 Ma age populations. Three of these formations show only Gondwanan provenance. Three others have a mixed Gondwanan-Laurentian signal, which is known to be typical for younger and/or more westerly sedimentary rocks and may indicate that they are the youngest deposits in the Merrimack belt (late Silurian to early Devonian) and/or have been deposited in the equivalent of the more westerly Central Maine basin. Detrital zircon age populations from the Tower Hill Formation, along the faulted contact between the Merrimack belt and Nashoba terrane, are different from either of these tectonic domains and may indicate that the boundary is complex.